تنمية قصر تمرنة القديمة بمىطقة الوادي - عبد المؤمن, شطي; Hebboul, Hanane, Directeur de thèse (My University, 2020)
The many cave paintings classified as World Heritage of Humanity as well as the various vestiges prove that life in the Algerian desert has existed for a long time. Among these ancient vestiges there are still archaeological traces such as ancient palaces. The Ksar Tamarana, municipality of Jamâa willaya of El Oued, is an old building that combines originality and intelligent integration with the environment. Despite its age, the Ksar still stands, defying time with its particular architecture, its traditional social structure and the natural beauty of the oasis that surrounds it. This bewitching beauty has captured the attention of architects, archaeologists, historians, domestic and international tourists. In order to revive this castle, it is necessary to restore it, to consolidate it by restructuring the pillars and foundations using traditional local materials for sustainable development and to promote tourism in the region
Laghouat : Université Amar Telidji - Département d'architecture Option : Patrimoine